Compaction and Collapse Characteristics of Dune Sand Stabilized with Lime-Silica Fume Mix - Mohammed Y. Fattah; Hasan H. Joni; Ahmed S. A. Al-Dulaimy (Earth Sciences Research Journal)
The purpose of this research is to assess the suitability of dune sands as construction materials. Moreover, such a goal is considered beneficial in determining appropriate methods for soil stabilization or ground improvement and to assessing the suitability of dune sands as subgrade layer for carrying roads and rail foundation. Dune sand samples were collected from a region in Baiji area in Salah-Aldeen governorate, North of Iraq. A grey-colored densified silica fume (SF) and lime (L) are used. Three percentages are used for lime (3%, 6%, and 9%), and four rates are used for silica fume (3%, 6%, 9% and 12%) and the maximum percentage of silica fume is mixed with the proportions of lime. Unsoaked California Bearing Ratio (CBR) on compacted dune sands treated dune sands with L-SF by mixing and cured for one day. The increasing in CBR ranged between 443 – 707% at 2.54 mm penetration and 345 – 410% at 5.08 mm penetration.